Application of resistance trainer for dynamic mechanical properties of conjugated polymer materials in daily physical strength tensile training - Hu, Wei (Frontiers in Chemistry, 2023)
Resistance training is an important means to improve human function and health level, and tensile training, as an important form, has significant effects on enhancing muscle strength, improving body flexibility, and promoting body coordination. Tensile training can provide external resistance through the use of resistance trainers, allowing muscle groups to work under load. This load stimulation can gradually promote muscle adaptation and enhancement. This article took conjugated polymer materials as the research object. By analyzing and testing their dynamic mechanical properties, the mechanical response characteristics of polyacetylene materials were analyzed using strain rate functions. The mechanical properties and deformation behavior of polyacetylene materials under different conditions were evaluated. It was found that conjugated polymer materials had good strength, elasticity, and wear resistance, making them suitable for making resistance trainers. The experimental results indicated that this study used a conjugated polymer material resistance trainer to train the testing personnel for a period of three months. During this training period, the tester's endurance increased by 21% to 29%, flexibility increased by 17% to 25%, and explosive power increased by 24% to 31%. The research results indicated that conjugated polymer materials had good plasticity and adjustability in the preparation of resistance training devices. Resistance devices of different shapes, sizes, and intensities can be prepared according to the needs and purposes of trainers, providing diverse and personalized choices for daily physical tensile training. The conjugated polymer material resistance trainer has significant effects and can effectively improve the physical fitness of testers. In addition, conjugated polymer materials exhibit excellent tensile performance and durability in resistance training, which can effectively meet the needs and requirements of trainers.